Operational feasibility of biomass combustion with in situ CO2 capture by CaO during 360 h in a 300 kWth calcium looping facility. (1st October 2016) - Diego, M.E.; Alonso, M.
Highlights: This work presents a 360 h in situ CaL experiment in a 300 kWth pilot plant. Remarkable stability was achieved for 360 h with a high CO2 capture efficiency. The results obtained prove the operational feasibility of the in situ CaL concept. Abstract: Simultaneous biomass combustion and CO2 capture using CaO, namely in situ calcium looping, has been proposed as a potential energy generation option with negative CO2 emissions. Previous pilot plant trials have already proven the technical feasibility of this process concept in pilot plants of up to 300 kWth . However, this study goes a step further and analyses the operational feasibility of these systems. For this purpose, a 360 h in situ calcium looping experiment was conducted in La Robla 300 kWth facility in continuous mode, which is the longest calcium looping test so far conducted at pilot plant scale, to the best of our knowledge. Operational stability was achieved and maintained throughout the entire experiment. Control of the facility was easily kept by performing slight modifications to the biomass and air feeding rates in order to ensure adequate temperatures and active bed inventories within the reactors, as well as sufficient solid circulation rates. As a result, high normalized CO2 capture efficiencies of over 80% were achieved during most of the test. The successful results obtained not only confirm the technical viability but also prove the operational feasibility of the in situ CO2 capture concept using CaO at high temperature at the 300 kWth plant scale, which is crucial for the future development of this type of CO2 capture technology.